Shelflife of whole fresh Lake Malawi Tilapia (Oreochromis species – Chambo) stored in ice - Kapute, F; Likongwe, J; Kang'ombe, J; Kiiyukia, C (African Scholarly Science Communications Trust, 2013)
Lake Malawi Tilapia (chambo) fish species is widely consumed and forms the most important commercial fishery in Lake Malawi. However, as a highly perishable commodity, knowledge regarding how long fresh fish would remain in acceptable and safe condition in storage is indispensable for consumers and processors. Presently, no such information exists for the Lake Malawi Tilapia in Malawi. A study was therefore conducted to estimate shelflife of whole fresh Lake Malawi Tilapia stored in ice (0 o C) for 21 days. Sensory, microbiological and pH analyses were conducted to describe changes in quality and freshness of the fish with storage time in ice. Shelflife of the fish was estimated between 16 and 18 days. A strong linear correlation (R2 =0.95) was observed between sensory demerit scores and storage time in ice. Total bacteria viable counts and pH at the time of sensory rejection of the fish were 1.6×107 cfu/g/cm2 and 5.84 respectively. Pseudomonas and Micrococcus bacteria were found in relatively high numbers throughout the storage period. The study demonstrated that like other tropical fish, Lake Malawi Tilapia has a relatively longer shelflife. The long storage life in ice of Lake Malawi Tilapia is advantageous to most small scale fresh fish sellers and processors especially from rural areas in Malawi who solely depend on ice as a sole and affordable way of preserving fresh fish.
Keywords: Ice storage